2023
DOI: 10.3390/w15071349
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Silver (Ag) and Silver Nanoparticles (AgNPs) in Aquatic Environment

Abstract: Nanomaterials, classified as emerging pollutants that are toxic to the environment, are known to bioaccumulate across different trophic levels in the aquatic ecosystem. This study therefore investigates the distribution of silver and silver nanoparticles (AgNPs) in the aquatic environment of Skudai River, Johor, Malaysia. Water, sediment, plant, and fish samples were collected seasonally along four sites along Skudai River between May 2018 and April 2019. All samples were subjected to Ag analysis using an indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…To investigate the most realistic effects of AgNPs on algae, we used environmentally relevant concentrations of silver that allowed 75% cell survival after 72 h in liquid BBM culture medium. Indeed, studies have shown that silver concentrations in Malaysian surface waters are as high as 0.505 mg L −1 [ 68 ] or as high as 10.16 mg L −1 [ 69 ], depending on the proximity to different factories, while previous predictions based on mathematical models estimate the upper limit of global silver concentration in environmental waters to be as high as 17 µg L −1 [ 70 ]. Considering that more than 130 tons of silver enter European aquatic ecosystems every year, 15% of which is in the form of AgNPs [ 71 ], and that silver production is increasing each year [ 71 , 72 ], the concentrations we use correspond to those that can realistically occur in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the most realistic effects of AgNPs on algae, we used environmentally relevant concentrations of silver that allowed 75% cell survival after 72 h in liquid BBM culture medium. Indeed, studies have shown that silver concentrations in Malaysian surface waters are as high as 0.505 mg L −1 [ 68 ] or as high as 10.16 mg L −1 [ 69 ], depending on the proximity to different factories, while previous predictions based on mathematical models estimate the upper limit of global silver concentration in environmental waters to be as high as 17 µg L −1 [ 70 ]. Considering that more than 130 tons of silver enter European aquatic ecosystems every year, 15% of which is in the form of AgNPs [ 71 ], and that silver production is increasing each year [ 71 , 72 ], the concentrations we use correspond to those that can realistically occur in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…These engineered nanomaterials (ENMs) have been integrated across diverse domains, spanning from facial masks, aerosol disinfectant sprays, textiles, and food packaging to environmental equipment and medical devices. , Nonetheless, the extensive utilization of these nanomaterials, while heralding significant benefits, also introduce a concomitant elevation in exposure risks, eliciting adverse effects on both the environment and human health. For instance, studies examining air quality have uncovered significant concentrations of TiO 2 particles, ranging from 21.2 to 277.3 μg/m 3 , and carbon black particles, with levels between 17 and 79 μg/m 3 . , Furthermore, water sample analyses have revealed the presence of up to 0.5 mg/L of Ag NPs, leading to substantial accumulation of silver in plants, ranging from 0.2 to 4.7 mg/kg, and in fish, with concentrations between 9.1 and 53.8 mg/kg) …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Furthermore, water sample analyses have revealed the presence of up to 0.5 mg/L of Ag NPs, leading to substantial accumulation of silver in plants, ranging from 0.2 to 4.7 mg/kg, and in fish, with concentrations between 9.1 and 53.8 mg/ kg). 17 Among the various potential routes of NP exposure, inhalation is the most perilous for human health. Inhaled NPs can penetrate the respiratory tract and localize in the terminal bronchi within the alveolar sacs of pulmonary lobules and alveoli, thus interacting with a multitude of constituents.…”
Section: ■ Introductionmentioning
confidence: 99%